Society, Medicine and Politics in Colonial India
1 online resource
Keywords: "The history of medicine and disease in colonial India remains a dynamic and innovative field of research, covering many facets of health, from government policy to local therapeutics. This volume presents a selection of essays examining varied aspects of health and medicine as they relate to the political upheavals of the colonial era. These range from the micro-politics of medicine in princely states and institutions such as asylums through to the wider canvas of sanitary diplomacy as well as the meaning of modernity and modernization in the context of British rule.The volume reflects the diversity of the field and showcases exciting new scholarship from early-career researchers as well as more established scholars by bringing to light many locations and dimensions of medicine and modernity. The essays have several common themes and together offer important insights into South Asias experience of modernity in the years before independence. Cutting across modernity and colonialism, some of the key themes explored here include issues of race, gender, sexuality, law, mental health, famine, disease, religion, missionary medicine, medical research, tensions between and within different medical traditions and practices and Indias place in an international context. This book will be of great interest to scholars and researchers of modern South Asian history, sociology, politics and anthropology as well as specialists in the history of medicine."--Provided by publisher.